Development of SciSpark Learning Media in Science and Social Studies (IPAS) to Optimize Critical Thinking in Elementary Schools - Yulia Maftuhah Hidayati; Sabekti Milan; Anif Sofyan (Jurnal Pedagogi dan Pembelajaran, 2026)
The limited use of interactive learning media in Natural and Social Sciences (IPAS) instruction has resulted in low student engagement and insufficient development of critical thinking skills. Existing classroom practices remain predominantly teacher-centered and textbook-based, limiting opportunities for higher-order thinking. This study aimed to develop and evaluate the effectiveness of SciSpark, an interactive digital learning medium designed to enhance elementary school students’ critical thinking skills in IPAS learning. The study employed a Research and Development (R&D) approach using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, combined with a quasi-experimental design. The participants were elementary school students assigned to experimental and control groups. Data were collected through classroom observations, teacher interviews, expert validation sheets, critical thinking tests, and student response questionnaires. Data analysis included expert validity assessment, descriptive statistics, independent samples t-test, and N-Gain analysis to measure improvements in students’ critical thinking skills. The findings indicated that SciSpark achieved a very high level of validity based on expert evaluations, received highly positive responses from students, and significantly improved critical thinking skills compared with conventional learning. This study concludes that SciSpark is an effective digital learning medium for supporting IPAS instruction while fostering students’ critical thinking skills. The findings imply that integrating interactive digital media with Higher-Order Thinking Skills (HOTS)-based activities, contextual simulations, and engaging learning experiences can serve as an innovative strategy for improving the quality of elementary science education.